2015
DOI: 10.1371/journal.pone.0131110
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Intraocular Forward Scattering and Corneal Higher-Order Aberrations on Visual Acuity after Descemet’s Stripping Automated Endothelial Keratoplasty

Abstract: PurposeTo assess the relationship of intraocular forward scattering and corneal higher-order aberrations (HOAs) with best spectacle corrected visual acuity (BSCVA) after Descemet’s stripping automated endothelial keratoplasty (DSAEK), and to compare these parameters between DSAEK and non-Descemet’s stripping automated endothelial keratoplasty (n-DSAEK) groups.MethodsThis retrospective study enrolled thirty eyes of 30 consecutive patients who underwent standard DSAEK, and who underwent successful phacoemulsific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 20 publications
1
9
0
Order By: Relevance
“…DPRPI has been successfully used to objectively classify the maturity of cataracts. 20, 22 A significant correlation between OSI and logarithm of the minimum angle of resolution (logMAR) but not between the size of higher order corneal aberrations and logMAR in patients status post corneal transplant has also been observed 23 , indicating DPRPI may be superior to Hartmann-Shack aberrometry in these cases. Encouragingly, OSI has been shown to detect corneal surface abnormalities; elevated OSI was observed over a 20 second course of no blinking in dry eye patients compared to no changes in controls.…”
Section: Introductionmentioning
confidence: 99%
“…DPRPI has been successfully used to objectively classify the maturity of cataracts. 20, 22 A significant correlation between OSI and logarithm of the minimum angle of resolution (logMAR) but not between the size of higher order corneal aberrations and logMAR in patients status post corneal transplant has also been observed 23 , indicating DPRPI may be superior to Hartmann-Shack aberrometry in these cases. Encouragingly, OSI has been shown to detect corneal surface abnormalities; elevated OSI was observed over a 20 second course of no blinking in dry eye patients compared to no changes in controls.…”
Section: Introductionmentioning
confidence: 99%
“…Hong et al demonstrated using the Fourier domain optical coherence tomography (OCT) that the linear deposits were located most deeply in the cornea, followed by granular deposits and diffuse haze moving anteriorly in eyes with GCD 8 . We previously demonstrated that the OSI was significantly associated with visual performance not only in normal eyes 9 , but also in post-descemet’s stripping automated endothelial keratoplasty eyes 10 . We consider that the objective assessment of forward scattering is of clinical help for predicting visual performance even in eyes with GCD.…”
Section: Discussionmentioning
confidence: 98%
“…Corneal HOAs were also measured with the Hartmann-Shack aberrometry (KR-9000, Topcon, Tokyo, Japan) for a 4-mm pupil, as described previously 10 . The root-mean-square of the third-order Zernike coefficients was utilized to represent third-order aberrations, the root-mean-square of the fourth-order coefficient to represent fourth-order aberrations.…”
Section: Methodsmentioning
confidence: 99%
“…), and significant correlations have been found between the OSI and the logMAR in patients after corneal transplantation (Kamiya et al. ). The OSI compares the integrated intensity contained in a ring between 0.20° and 0.33° (degrees), that is, between 12 and 20 min of arc, with the integrated intensity contained in the central area of the DP image within 1 min of arc.…”
Section: Introductionmentioning
confidence: 99%